Analisis Gaya Komunikasi Pemimpin dalam Meningkatkan Kinerja Karyawan di Pierogi Pierogi Bali - Putu Suparna; Filomena Sartika (MUKASI: Jurnal Ilmu Komunikasi, 2026)
Communication is an organization plays an important role in creating an effective working relationship between leaders and employees. The communication style applied by leaders has a major influence on employee comfort, motivation and productivity. The purpose of this study is to analyze the communication style used by leaders in improving employee performance at Pierogi Pierogi Bali. The method used is qualitative descriptive, with interview techniques, observation and documentation studies. The technique for determining informants in this study used purposive sampling technique. The results of this study indicate that the dominant communication style is controlling style, which is shown through the assertiveness of one-way communication. Leaders also show a tendency to use structuring style, shown by the delivery of systematic and clear instructions, as well as dynamic style which tends to be aggressive and causes discomfort for employees. This communication style has a direct influence on employee performance. Therefore, it is important for a leader to adjust his communication style to the needs and characteristics of the team in order to create a healthy work environment and support sustainable performance improvement.